Some Remarks on ius vitae ac necis and ius exponendi - Tamás Nótári (Journal on European History of Law)
A Roman pater familias was entitled to the following positive rights: ius vitae ac necis, ius exponendi, ius vendendi and ius noxae dedendi. What follows is an in-depth analysis of the changes in ius vitae ac necis and ius exponendi. Ius vitae ac necis denotes right of disposal over the life and death of a filius/filia familias, while ius exponendi the right to expose newborn infants. Exposing a child often contained its death or wilful murder; e.g., in case of a deformed child when the aim was to get the family or the community rid of prodigium representing ill luck. Therefore, it seems to be more proper to discuss the rights a father had against newborn infants—no matter if they applied to killing or only exposing the child—as part of ius exponendi since killing or exposing children was several times limited and sanctioned in a single imperial decree. Originally, ius vitae ac necis was sacral and punitive law power. Its sacral character came to the front when killing a deformed child since this right is the component of the father’s power over his newborn infant, and this will be discussed under the heading ius exponendi; its punitive law aspect will become obvious when it is used against an adult child. This paper, first, intends to describe changes in ius vitae ac necis, and dwell on the restrictions and rules of procedure of exercising it (I.). After that, changes in ius exponendi will be followed up, with special regard to the regulation of the legal status of the exposed child (II.).